What teachers think about teacher unions: a stratified probability survey of central Gauteng teachers - Siewierski, Cherly Leigh-Anne (My University, 2015)
Historically, qualitative literature and media reporting reflect the notion that teacher unionism in South Africa is an exercise in polarities: with one larger form of militant teacher unionism represented by SADTU focusing on teacher benefits and employing any means necessary to obtain its goals, and another, more ‘restrained’ form of teacher unionism represented by the NUE and SAOU which demonstrates a greater concern with professionalism and teacher development. There is, however, little reliable, generalisable evidence that this ‘either/or,’ militant vs. professional unionism is, in fact, the experienced reality of those most directly affected: South African teachers themselves. As a result, the seemingly patent unionist vs. professional union ‘archetypes’ that pervade media reports and qualitative literature are difficult to confirm or reject. In an attempt to contribute to the quantitative literature on teacher unionism in South Africa, this report describes the perceptions and opinions of 288 central-Gauteng teachers, who represent three of the largest South African teacher unions. A quantitative methodology using a stratified probability sample and survey questionnaire was employed to engage in this topic as objectively as possible. Explored themes relating to union fees, membership, benefits, teaching and learning, performance, and strike action revealed some notable incongruities with existing literature. Firstly, despite some accounts suggesting otherwise, respondents in this study report a general satisfaction with their unions. Secondly, although the majority reject the principle of forced union-membership, most respondents indicate that they would, nevertheless, remain voluntarily unionised. Thirdly and perhaps more significantly, in contrast with the historical ‘militant vs. professional’ conceptions of teacher unions, this study found more similarities in the attitudes of apparently polar-opposed union members than differences. As more recent local and international literature has argued then, this report’s findings support the argument that polarised union ‘types’ no longer appear to be as distinct as they once may have been. Perhaps the finding of most import of this study though, is that despite the glut of media reports which suggest an-almost innate desire of SADTU teachers to strike, a massive 76% of sampled teachers in this study - including those reporting SADTU-affiliation - rejected outright the use of unprotected strikes to achieve union goals. This finding calls into question the use of illegal strikes as a negotiation tool of more ‘militant’ teacher unions in South Africa, and should encourage teacher unions to explore alternative negotiation tools for future union practice.
A research report For The School of Education, University of Witwatersrand, in partial fulfilment of the requirements of the degree of Master of Education 13 February 2015